Prevalence of Dermatophytes in The Haircoat of Red Deer (Cervus elaphus) in The Stelvio National Park, Italy. (International Journal of Health, Animal Science and Food Safety, 2014)
Dermatophytosis has been described in wildlife, but the literature reporting dermatophyte prevalence in deer is incomplete. To determine the prevalence of dermatophytes and to evaluate the hypothetical role of asymptomatic carriers hair samples were collected from 30 legally hunted wild red deer (Cervus elaphus) in the Stelvio National Park, Italy. All deer were visually examined for dermatologic lesions and the coat was brushed using a modified Mackenzie collection method. A small sample of hair was used for trichography and subsequently fungal culture was performed on the hair samples. Macroscopic and microscopic examinations were used to identify dermatophytes, saprophytic fungi and yeasts. None of the deer had visible cutaneous lesions. No dermatophyte spores or hyphae were found on trichography and, when hair samples were cultured, there was no colour change on DTM in any sample nor was any dermatophyte colony grown. Only saprophytic fungi were grown, predominantly Alternaria spp., Mucor spp., Cladosporium spp. These results suggest that the red deer of Stelvio National Park do not seem to be asymptomatic carriers of dermatophytes and confirm that it is unlikely that the deer act a reservoir for transmission of dermatophytes  to other wild animals, livestock or people living locally.
Keywords: Cervus elaphus; Dermatophytes; Fulgal flora; Prevalence; Red deer; Stelvio national park